Of a Free Man: Downplaying colonial crisis in the discourse of V. S. Naipaul - Karim, Mohammad Rezaul; Sharma, Ramesh; Banu, Sameena (Research Journal in Advanced Humanities, 2023)
V. S. Naipaul was one of the most prolific writers of the modern time. His writings fluctuate between a sense of psychological crisis triggered by collapse of colonization towards the midst Twentieth century and the meaning of a free man. In other words, his writings look at what does it take to be a free man in a decolonized world; whether this freedom is achieved at the cost of the crisis or within the crisis, or whether the crisis itself is a part of the freedom. However, the understanding of the answer to these questions in his readers seems to be very limiting. The sense of the crisis and the freedom in him has been understood as something narrowing and damaging. However, this can be contested and the sense of crisis, its cause and affect can be best understood with a point of reference to the idea of “irresponsibility” and “contamination” in Jacques Derrida and Gayatri Spivak. His discourse is a meditation on several world contexts- Indian, European, African and Caribbean for instance. This paper contends to say and establish that the sense of crisis in Naipaul as far as his writings on the Caribbean context are concerned, is not damaging, rather it is an enabling phenomenon ensuring a sense of freedom.